Effects of erythromycin on γ-glutamyl cysteine synthetase and interleukin-1β in hyperoxia-exposed lung tissue of premature newborn rats - Cheng Cai; Gang Qiu; Xiaohui Gong; Yihuan Chen; Huanhu Zhao (Elsevier, 2014)
Objective: To explore the effect of erythromycin on hyperoxia-induced lung injury. Methods: One-day-old preterm offspring Sprague-Dawley (SD) rats were randomly divided into four groups: group 1, air + sodium chloride; group 2, air + erythromycin;group 3, hyperoxia + sodium chloride; and group 4, hyperoxia + erythromycin. At one, seven, and 14 days of exposure, glutathione (GSH) and interleukin-1 beta (IL-1 beta) were detected by double-antibody sandwich enzyme-linked immunosorbent assay (ELISA), and bicinchoninic acid (BCA) was used to detect GSH protein. γ-glutamine-cysteine synthetase (γ-GCS) mRNA was detected by reverse transcription-polymerase chain reaction (RT-PCR). Results: Compared with group 1, expressions of GSH and γ-GCS mRNA in group 3 were significantly increased at one and seven days of exposure (p < 0.05), but expression of γ-GCS mRNA was significantly reduced at 14 days; expression of IL-1 beta in group 3 was significantly increased at seven days of exposure (p < 0.05), and was significantly reduced at 14 days. Compared with group 3, expressions of GSH and γ-GCS mRNA in group 4 were significantly increased at one, seven, and 14 days of exposure (p < 0.05), but expressions of GSH showed a downward trend at 14 days; expression of IL-1 beta in group 4 was significantly reduced at one and seven days of exposure (p < 0.05). Conclusions: Changes in oxidant-mediated IL-1 beta and GSH are involved in the development of hyperoxia-induced lung injury. Erythromycin may up-regulate the activity of γ-GCS, increasing the expression of GSH, inhibiting the levels of oxidant-mediated IL-1 beta and alleviating hyperoxia-induced lung injury via an antioxidant effect. Resumo: Objetivo: Explorar o efeito da eritromicina sobre lesões pulmonares induzidas por hiperóxia. Métodos: Uma prole de ratos Sprague-Dawley (SD) prematuros com um dia de vida foi dividida aleatoriamente em quatro grupos: grupo 1 ar + cloreto de sódio, grupo 2 ar + eritromicina, grupo 3 hiperóxia + cloreto de sódio e grupo 4 hiperóxia + eritromicina. Com um, sete e 14 dias de exposição, foram detectadas Glutationa (GSH) e Interleucina-1 beta (IL-1 beta) pelo ensaio imunossorvente ligado à enzima (ELISA), e o ácido bicinconinico (BCA) foi utilizado para detectar a proteína GSH. O mRNA da γ-glutamil-cisteina-sintetase (γ-GCS) foi detectado por reação em cadeia da polimerase via transcriptase reversa (RT-PCR). Resultados: Comparadas ao grupo 1, as expressões do mRNA da GSH e da γ-GCS no grupo 3 aumentaram significativamente com um e sete dias de exposição (p < 0,05), porém a expressão de mRNA da γ-GCS diminuiu significativamente aos 14 dias; a expressão de IL-1 beta no grupo 3 aumentou significativamente aos 7 dias de exposição (p < 0,05) e diminuiu significativamente aos 14 dias. Comparadas ao grupo 3, as expressões do mRNA da GSH e da γ-GCS no grupo 4 aumentaram significativamente com um, sete e 14 dias de exposição (p < 0,05), porém as expressões de GSH mostraram uma tendência de queda aos 14 dias; a expressão de IL-1 beta no grupo 4 foi reduzida significativamente com um e sete dias de exposição (p < 0,05). Conclusões: As variações de IL-1 beta e GSH mediadas por oxidantes estão envolvidas no desenvolvimento de lesão pulmonar induzida por hiperóxia. A eritromicina poderá regular positivamente a atividade da γ-GCS, aumentando a expressão de GSH, inibindo os níveis de interleucina-1beta mediada por oxidante e aliviando a lesão pulmonar induzida por hiperóxia por meio de um efeito antioxidante. Keywords: Erythromycin, Hyperoxia, Lung injury, Glutathione, Interleukin-1-beta, Palavras-chave: Eritromicina, Hiperóxia, Lesão pulmonar, Glutationa, Interleucina-1 beta